2010
DOI: 10.1002/cssc.201000080
|View full text |Cite
|
Sign up to set email alerts
|

A Bio‐Metal–Organic Framework for Highly Selective CO2 Capture: A Molecular Simulation Study

Abstract: A recently synthesized bio-metal-organic framework (bio-MOF-11) is investigated for CO(2) capture by molecular simulation. The adenine biomolecular linkers in bio-MOF-11 contain Lewis basic amino and pyrimidine groups as the preferential adsorption sites. The simulated and experimental adsorption isotherms of pure CO(2), H(2), and N(2) are in perfect agreement. Bio-MOF-11 exhibits larger adsorption capacities compared to numerous zeolites, activated carbons, and MOFs, which is attributed to the presence of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 40 publications
2
80
0
Order By: Relevance
“…However, the number of computational studies on bio-MOFs is very limited in the literature. Chen and Jiang (Chen and Jiang, 2010) investigated separation performance of bio-MOF-11 for CO 2 /N 2 and CO 2 /H 2 mixtures using molecular simulations. The high adsorption selectivity (375) computed for CO 2 /H 2 mixture at 298 K at 4 bar was attributed to the presence of Lewis-basic sites in adenine which improves the interactions with CO 2 molecules.…”
Section: Toc Graphicmentioning
confidence: 99%
“…However, the number of computational studies on bio-MOFs is very limited in the literature. Chen and Jiang (Chen and Jiang, 2010) investigated separation performance of bio-MOF-11 for CO 2 /N 2 and CO 2 /H 2 mixtures using molecular simulations. The high adsorption selectivity (375) computed for CO 2 /H 2 mixture at 298 K at 4 bar was attributed to the presence of Lewis-basic sites in adenine which improves the interactions with CO 2 molecules.…”
Section: Toc Graphicmentioning
confidence: 99%
“…The dispersive interactions of framework atoms and cations were modeled by the Universal Force Field (UFF) (Rappe et al, 1992), as listed in Table 1. A number of simulation studies have shown that UFF can accurately predict gas adsorption in various MOFs (Babarao and Jiang, 2008;Chen and Jiang, 2010;Skoulidias and Sholl, 2005;Garberoglio et al, 2005). CO 2 was modeled by a three-site rigid molecule, in which the partial charges on C and O atoms were q C ¼0.576e and q O ¼ -0.288e (e¼1.6022 Â 10 -19 ) (Hirotani et al, 1997).…”
Section: Molecular Simulation Of Adsorption and Diffusionmentioning
confidence: 99%
“…In the past decades, a number of methods have been proposed to solve the problem including cryogenic distillation, amine scrubbing, and sorbent adsorption [1]. Among these methods, pressure swing adsorption (PSA) technology and membrane separation based on porous materials are known to be efficient and affordable processes for CO2 removal from flue streams.…”
Section: Introductionmentioning
confidence: 99%